Harnessing emotional and cultural intelligence for corporate sustainability in Indonesia: Examining psychological contracts, task interdependence, and environmentally sustainable project performance - Asep Marfu; Hafid Abbas; Ahman Sya; Agung Purwanto; Nadiroh; Bagus Sumargo; Septantri Shinta Wulandari; Daiman; Christin A. Malaihollo; Syakyakirti; David Tanubrata; Dewi Indah Pratiwi (Sustainable Futures)
This study aims to examine the impact of emotional intelligence, cultural intelligence, and psychological contracts on task interdependence and environmental complexity, and how these factors influence environmentally sustainable project performance. Using a quantitative research approach, the study employs partial least squares structural equation modeling to analyze survey data collected from project managers and team members across various industries in Indonesia. The key findings reveal that emotional intelligence and cultural intelligence positively influence task interdependence and environmental complexity, which, in turn, enhance environmentally sustainable project performance. However, the impact of psychological contracts on task interdependence and environmental complexity was not supported. This research contributes to the growing body of knowledge on corporate sustainability by highlighting the role of emotional and cultural intelligence in fostering teamwork and managing environmental challenges. The originality of this study lies in its focus on the Indonesian context, offering valuable insights into the dynamics of sustainability in the region. The findings suggest that organizations should invest in developing emotional and cultural intelligence to improve collaborative efforts and effectively navigate environmental complexities for sustainable project outcomes. Future research could explore the influence of other organizational factors on sustainability performance in diverse cultural and economic settings.